Silêncio e invisibilidade: a atitude discriminatória de professores diante da homossexualidade na escola - Marsiglia, Denys Munhoz (2009)
This abstract has as a purpose to discuss the teacher s prejudice and discrimination attitude towards homosexuality in schools. It was investigated, through research, what society and school positioning is on the issue of sexuality, how homosexuality is identified, how it is considered in the context of the school, and also explore the concepts of prejudice and discrimination, and the resources to overcome them. Used, among others, the Abramovay (2004), Aquino (1997, 1998, 2000), Brazil / MEC / SEF (1998), Chaui (1984), Louro (1997a, 1997b, 1998, 1999, 2001), and Rios (2006a, 2006b, 2006c, 2006d). It was found that people s sexual identity and gender are interdependent and socially and historically constructed and that societies establish what is considered a normal pattern for the sexual behavior of individuals. The homosexuality appears as a deviant behavior, and thus subject of discrimination, despite movements of reaction against that. To the extent that the school is a place of socialization and values, we see reflected in it a discrimination attitude towards homosexuality on the part of pupils and teachers. The use of ethics as critical reflection on the values that underpin the actions and relations of individuals and groups in society, turns out to be an important element to overcome that attitude. Then it is established the need of ethics in the teacher s initial and continuing training in their daily work, in the curricular organization and in the planning and development of the school pedagogical projects.